Design of Customer Satisfaction Criteria for Telecommunications Operators: Fixed Broadband Services - Ellin Devihana Pratiwi; Catur Apriono (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2023)
Customer dissatisfaction is an opportunity lost for telecommunications operators in fixed broadband services in expanding its market, it is indicating that the criteria used in designing the loyalty program that being provided to customer are still less precise. This research aims to provide recommendations for telecommunications operator loyalty programs for fixed broadband services based on customer satisfaction’s criteria. This research uses DEMATEL-Based ANP (DANP) and Simple Additive Weighting (SAW) method to get assessment of loyalty program that best fits the customer satisfaction’s criteria. This research resulted in 5 dimensions and 22 criteria of customer satisfaction for telecommunications operators in fixed broadband services, where the dimension that most influences is resource and the dimension that is most influenced is relationship. The best loyalty program for telecommunications operators in fixed broadband services at PT X is High Value Customer (HVC), while the worst loyalty program is Customer Application.